Karakteristik Leukemia Limfoblastik Akut pada Anak di Rumah Sakit Kanker âDharmaisâ 2000-2008 - RINI, ANKY TRI; AISY, MURURUL; ASRI, YUNI; -, EDI (Indonesian Journal of Cancer, 2010)
Acute lymphoblastic leukemia (ALL) is the most common cancer found in children below 14 years old. It characterized by abnormal white blood cell proliferation which replace normal bone marrow componentÂ  with pallor,Â  headache, organomegaly, fever, bone pain and bleeding as itâs clinical manifestation. AcuteÂ  lymphoblastic Leukemia (ALL) is very important problem in childhood cancer. As one strategy to improve cancer management, specially ALL, epidemiology description and patient outcome is needed. Based on our study inÂ  Dharmais Cancer Hospital (2000-2008), ALL is frequent in boy and particularly lie between 1-5 years old. ALL L1 is the most common type of ALL, and majority cases are standard risk. We observed 44,9% mortality,survive 27,5 %. Unfortunately there were many patients loss to follow upÂ  (27,5%) andÂ  event free survival rates for ALL inÂ  Dharmais Cancer Hospital is 38,1%.